Morphometrics and taxonomic update to the Sri Lankan Aponogetonaceae - Manawaduge, Chapa G; Yakandawala, Deepthi (Phytotaxa, 2018)
The recent studies on Sri Lankan Aponogeton underline the necessity of a taxonomic revision for the genus; especially with the recent discovery of two new endemic taxa and their described morphological affinities, revealing some misconceptions in the key morphological features used in identification and the overlapping morphology of the species within the genus. Accordingly, a morphometric analysis was carried out with 78 field collected specimens representing all six Sri Lankan Aponogeton species. The results indicate that A. kannangarae, a recently described endemic species which has been stated as closely resembling A. rigidifolius, is more similar to A. jacobsenii, with shared morphological characters, raising doubts if it is a distinct species. Further, the endemic A. jacobsenii, previously described and illustrated as a species with rarely occurring floating leaves, has been now described as with no floating leaves. Based on the results, a taxonomic update is presented with a key, full synonymy, descriptions and photographs.